New insights in online fashion retail returns from a customers' perspective and their dynamics - Björn Stöcker; Daniel Baier; Benedikt M. Brand (Journal of Business Economics, 2021)
Returns are an inconvenient problem in the mail-order business, not only for the merchant but also for the customer. With an estimated return rate of 50% in the fashion sector, the seller has to deal with the expense of restocking and possibly reprocessing, the buyer, who must reship the return, and the environment. We do not consider returns to be generally bad, but rather an explicit, integral part of the online business model. Therefore, we investigate potentially suitable measures to avert or avoid returns in the pre-purchase, purchase, and post-purchase phases. We look at current and technological developments in return management and the most critical drivers for fashion assortment returns. The measures we investigate deliver a holistic view of the issue and target all three purchase phases. The resulting measures were assessed via an online questionnaire with 8393 participants (customers of a German fashion online retailer) to impact customer satisfaction using Kano's method. There are clear measures that promise high customer satisfaction (such as 360° view) and a clear hierarchy regarding monetary and non-monetary measures. By applying a new method, the segmented Kano perspective, we found different customer segments, which are different in their expectations towards returns. That allowed us to conclude dynamics regarding return management. This assessment is followed by discussing the results, conclusions, and indications for further research fields.
Keywords: M21; M31; 650; Returns; Drivers for returns; Avoiding and averting returns; Kano (method); Segmented kano perspective; Customer perspective; Kano dynamics